Incidental Unruptured Intracranial Aneurysms Do Not Impact Outcome in Patients With Acute Cerebral Infarction - Wu, Xuan; Duan, Zuowei; Liu, Yihui; Zhou, Changwu; Jiao, Zhiyun; Zhao, Yi; Tang, Tieyu (Frontiers in Neurology, 2021)
Background: This study was to examine the patients with ACI treated at a single center over 9 years and who underwent UIA screening by three-dimensional time-of-flight magnetic resonance angiography (3D-TOF-MRA), and to explore the factors associated with prognosis. Methods: The outcome was the modified Rankin scale (mRS) score at 90 days after stroke onset. The outcome was classified into a good prognosis (mRS score of 0-2 points) and poor prognosis (mRS score of 3-6 points). Results: UIAs were found in 260 (6.5%) of 4033 patients with ACI; 2543 (63.1%) had a good prognosis, and 1490 (36.9%) had a poor prognosis. There was no difference in prognosis between the two groups (P=0.785). The multivariable analysis showed that age (OR=1.009, 95%CI: 1.003-1.014, P=0.003), diabetes (OR=1.179, 95%CI: 1.035-1.342, P=0.013), ischemic stroke history (OR=1.451, 95%CI: 1.256-1.677, P<0.001), and baseline NIHSS score (OR=1.034, 95%CI: 1.018-1.050, P<0.001) were independently associated with the 90-day prognosis in patients with ACI. The presence of incidental UIA was not associated with prognosis after ACI. Conclusions: Thrombolytic therapy was not affected by the presence of UIA in patients with ACI. Age, diabetes, ischemic stroke history, and baseline NIHSS score were independently associated with the early prognosis of patients with ACI.